Philosophical and Cultural Analysis of Oksana Chepelyk's Art Project "Refraction of Reality" - Iryna Maslikova; Svitlana Stoian (International Society of Philosophy and Cosmology, 2022)
The article carries out a philosophical and cultural analysis of the creative works by Ukrainian artist Oksana Chepelyk on the example of her art project "Refraction of Reality". Ukrainian artist tries to reflect on the problem of modern human's existence in a technocratic world. The artist actively uses latest media technologies to visualize the total inclusion of a person in the technocratic reality. Despite the criticism of many modern thinkers, among whom the most radical position about modern art is taken by Jean Baudrillard, the authors this research justify necessity of improvement reality via new media technologies. The modern person, in particular the creative persan, is clearly aware that it is impossible to change the surrounding reality with all its innovations, and it is only possible to adapt to these changes, using technologies to their advantage, minimizing their harm as much as possible.